Conflicto social e inseguridad ciudadana en la parroquia Guanujo del cantón Guaranda provincia Bolívar: 2021. - Barragán Ocampo, Jimena Graciela (2023)
Citizen insecurity has been caused by several factors such as crime, poverty, lack of employment, lack of public policies that are aimed at correcting certain gaps that exist in society, it is thus determined that the social conflicts that Ecuador has experienced In recent years, for example, the most recent and chaotic was the strike in October 2019, which escalated to the level of crisis and left unfortunate consequences for the entire country. In addition, many conflicts are due to corruption and the economic crisis that Ecuador is going through, which has caused job loss, decreased purchasing power of people, increased poverty, crime and inequality; Therefore, the main objective of this research is to determine if citizen insecurity, which is caused by crime, causes social conflict and at what level it would develop. When the subject of citizen insecurity is taken, we refer to certain acts that physically and psychologically transgress citizenship and its effects are negative on the well-being and quality of life of citizens, reveal the causes that originate said conflicts and at the same time discover what generates citizen insecurity would improve the quality of life of the population, it is concluded that citizen insecurity in its most objective dimension causes physical and economic damage with an effect of the deterioration of the health, economic and labor of the people who suffer directly from these facts and another part causes a perception of insecurity, fear and distrust that affects cognitively and physically-psychologically, with changes in their attitudes, habits and personal relationships, which trigger citizens to have several losses at work and social level. An exploratory, documentary and explanatory research was developed in order to delve into the issue raised and seeking general knowledge of it, it was also possible to determine the characteristics and results of the problem outlined; The methodology used allowed this information to be collected in a transcendental way through the application of interviews and surveys to a certain part of the residents of the Guanujo parish of the Guaranda canton. xvii The present investigation seeks as a result to determine if citizen insecurity is due to the consequences generated by social conflicts.